H∞ filter-based online battery state-of-charge estimator for pure electric vehicles - Castillo, Gaudan Albert Chekov L. (2011)
This research describes the development of an online battery SOC estimator using an H-infinity filter for pure electric vehicles equipped with a Lead Acid battery pack. The procedure followed in the computation of the battery parameters is discussed along with the methods used in the selection of H-infinity filter parameters. Asimulation based H-infinity estimator is presented together with a hardware based estimator. An analysis of the results is shown in the later chapters showing a hardware estimator capable of providing outputs with errors as low as 6%. Finally, a discussion on the limitations of the hardware estimator together with a few recommendations for improvement is presented.